Pengaruh Bermain Mobile Legends terhadap Kesehatan Mental Mahasiswa UKM E-sports Universitas PGRI Adi Buana Surabaya - Abdillah Wilfriyantoni Rio Wildan; Luqmanul Hakim; Eka Kurnia Darisman (MAN Insan Cendekia Jambi, 2026)
This study aims to analyze the effect of playing Mobile Legends on the mental health of students who are members of the E-sports Student Activity Unit at PGRI Adi Buana University Surabaya. The increasing popularity of online games, particularly Mobile Legends, has led to various impacts on players’ psychological conditions, both positive and negative. This research employed a quantitative approach using a descriptive survey design. The population consisted of students who are members of Adi Buana E-sports (ABE), while the sample included 20 students from the Mobile Legends division selected through random sampling. Data were collected using a questionnaire containing indicators of mental health before and after playing Mobile Legends. The results of data analysis showed a significance value of 0.007 (< 0.05), indicating that playing Mobile Legends has a significant effect on students’ mental health. These findings suggest that gaming activities can influence players’ psychological conditions, depending on their ability to manage playing time and regulate emotional responses during gameplay.